The emperor of all maladies : a biography of cancer - Mukherjee, Siddhartha (New York : Scribner, 2011)
A magnificently written "biography" of cancer--from its origins to the epic battle to cure, control, and conquer it.
"Of blacke cholor, without boyling" -- An impatient war -- "Will you turn me out if I can't get better?" -- Prevention is the cure -- "A distroted version of our normal selves" -- The fruits of long endeavors
Includes bibliographical references (p. 537-541) and index.
Keywords: Cancer -- History; Leukemia -- History